2022
DOI: 10.1177/00332941221133006
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Social Anxiety on the Relationship Between Internet Addiction and Aggression in Teenagers

Abstract: The purpose of this study was to investigate the effect of “internet addiction level” on “aggression level” among teenagers and to examine the mediating role of “social anxiety level” on this effect. The study participants consisted of 958 students attending private teaching institutions for university preparation in Turkey. Data was collected from voluntary participants through data collection forms delivered to the management of these institutions. “Sociodemographic Characteristics Questionnaire Form”, “Youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Fear of negative evaluation (FNE) refers to the individual's fear of potential and possible negative evaluations of others [6] . In the cognitivebehavioural model, the most important manifestation of social anxiety is the fear of negative evaluations, which is an individual's assessment of the possibility of negative evaluations in social situations [7] .At the same time, some studies have found that social anxiety is closely related to individuals' aggressive behaviour, that is, the more severe social anxiety, the more severe their aggressive behaviour [8,9] . Therefore, the following hypotheses were made: fear of negative evaluation is positively related to aggressive behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Fear of negative evaluation (FNE) refers to the individual's fear of potential and possible negative evaluations of others [6] . In the cognitivebehavioural model, the most important manifestation of social anxiety is the fear of negative evaluations, which is an individual's assessment of the possibility of negative evaluations in social situations [7] .At the same time, some studies have found that social anxiety is closely related to individuals' aggressive behaviour, that is, the more severe social anxiety, the more severe their aggressive behaviour [8,9] . Therefore, the following hypotheses were made: fear of negative evaluation is positively related to aggressive behaviour.…”
Section: Introductionmentioning
confidence: 99%